Electrochemical generation of hydrogen peroxide - Goh, Kiat Yin (Nanyang Technological University, 2023)
The effects of greenhouse gases, primarily from carbon dioxide emissions, have had a significant impact on the environment. Traditional methods of producing hydrogen peroxide for commercial use are known to be resource-intensive and environmentally damaging. This research paper aims to investigate the feasibility of electrochemical generation of hydrogen peroxide (H2O2) as a sustainable alternative to traditional commercial methods. This study focuses on finding the optimal catalytic mass loading of Modified Carbon Black (MCB) (0.05 mg cm-2, 0.5625 mg cm-2 and 1.125 mg cm-2) for achieving high yields of H2O2 through membrane electrode assembly (MEA) porous solid electrolyte cell. Rotating Ring Disk Electrode experiments were conducted to determine the activity and selectivity of the different mass loadings. Results indicate that the 0.5625 mg cm-2 mass loading produced the highest current density and yield of H2O2 in the MEA experiment, although its selectivity and activity were not the best among the 3 mass loadings. 0.05 mg cm-2 mass loading exhibited the best selectivity while 1.125 mg cm-2 had the highest activity but lower selectivity due to its participation in 4e- ORR. The findings suggest that electrochemical generation of H2O2 using MCB as a catalyst could offer an eco-friendly and sustainable method for decentralized production of H2O2.